2004
DOI: 10.1080/09553000400017671
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic potential of 5‐[125I]iodo‐2′‐deoxyuridine and methotrexate in the treatment of advanced neoplastic meningitis

Abstract: Intrathecal injection of MTX-(125)IdUrd is efficacious in the therapy of advanced intrathecal tumours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 20 publications
1
19
0
Order By: Relevance
“…Similar findings occur with [ 123 I]UdR [40]. Therapeutic doses of [ 125 I]UdR injected intrathecally into rats with intrathecal tumours significantly delay the onset of paralysis, and the coadministration of methotrexate, an antimetabolite that enhances IUdR uptake by DNA-synthesising cells, substantially enhances the therapeutic efficacy (Figure 9) as exemplified by a 5 -6-log tumour cell kill and the curing of ∼ 30% of the tumour-bearing rats [41,42].…”
Section: Nonenergetic Particlessupporting
confidence: 68%
See 1 more Smart Citation
“…Similar findings occur with [ 123 I]UdR [40]. Therapeutic doses of [ 125 I]UdR injected intrathecally into rats with intrathecal tumours significantly delay the onset of paralysis, and the coadministration of methotrexate, an antimetabolite that enhances IUdR uptake by DNA-synthesising cells, substantially enhances the therapeutic efficacy (Figure 9) as exemplified by a 5 -6-log tumour cell kill and the curing of ∼ 30% of the tumour-bearing rats [41,42].…”
Section: Nonenergetic Particlessupporting
confidence: 68%
“…The extreme degree of cytotoxicity observed with DNAincorporated Auger-electron emitters has been exploited in experimental radionuclide therapy. In most of these in vivo studies, the thymidine analogue 5-iodo-2′-deoxyuridine (IUdR) has been used [39][40][41][42], and the results have shown excellent therapeutic efficacy. For example, the injection of [ 125 I]UdR into mice bearing an intraperitoneal ascites ovarian cancer has led to a 5-log reduction in tumour cell survival [39].…”
Section: Nonenergetic Particlesmentioning
confidence: 99%
“…Indeed, other studies have demonstrated that the efficacy of Auger electron radiotherapy can be significantly enhanced by MTX. For example, the administration of MTX before the injection of 5-[ 125 I]iodo-29-deoxyuridine ( 125 IUdR) in rats with intrathecal TE-671 human rhabdomyosarcoma enhanced 125 IUdR uptake by tumor cells and augmented the therapeutic efficacy of this Auger electron-emitting radiopharmaceutical (36). Paclitaxel, docetaxel (Taxotere; SanofiAventis), gemcitabine, topotecan, 5-fluorouracil, doxorubicin, tirapazamine, or halogenated pyrimidines have also been combined with targeted a-or b-radioimmunotherapy and have been shown to inhibit the growth of various malignant cell lines in vitro or provide antitumor effects in mouse xenograft models and in human clinical trials more effectively than either treatment alone (15,16).…”
Section: Discussionmentioning
confidence: 99%
“…Further analysis indicates that 17% of SSBs and 100% of DSBs take place within the plasmid molecule in which an 125 IEH molecule decays, whereas 83% of SSBs are formed in neighboring plasmid DNA molecules. ᭧ 2006 by Radiation Research Society its potential for use in cancer therapy (6)(7)(8). The decay of this Auger-electron emitter produces a cascade of extremely low-energy electrons, ϳ21 on average: of these, ϳ18 electrons have a range Ͻ100 nm and ϳ8 electrons travel Ͻ2 nm (9).…”
mentioning
confidence: 99%